Orientation of Laurdan in Phospholipid Bilayers Influences Its Fluorescence: Quantum Mechanics and Classical Molecular Dynamics Study - Wasif Baig, Mirza; Pederzoli, Marek; Jurkiewicz, Piotr; Cwiklik, Lukasz; Pittner, Jiri (Molecules (Basel, Switzerland), 2018)
Fluidity of lipid membranes is known to play an important role in the functioning of living organisms. The fluorescent probe Laurdan embedded in a lipid membrane is typically used to assess the fluidity state of lipid bilayers by utilizing the sensitivity of Laurdan emission to the properties of its lipid environment. In particular, Laurdan fluorescence is sensitive to gel vs liquid⁻crystalline phases of lipids, which is demonstrated in different emission of the dye in these two phases. Still, the exact mechanism of the environment effects on Laurdan emission is not understood. Herein, we utilize dipalmitoylphosphatidylcholine (DPPC) and dioleoylphosphatidylcholine (DOPC) lipid bilayers, which at room temperature represent gel and liquid⁻crystalline phases, respectively. We simulate absorption and emission spectra of Laurdan in both DOPC and DPPC bilayers with quantum chemical and classical molecular dynamics methods. We demonstrate that Laurdan is incorporated in heterogeneous fashion in both DOPC and DPPC bilayers, and that its fluorescence depends on the details of this embedding.
Keywords: fluorescence; laurany; Molecular Dynamics Simulation; Lipid Bilayers; lipidové dvojvrstvy; 1,2-dipalmitoylfosfatidylcholin; Quantum Theory; Laurates; simulace molekulární dynamiky; fosfatidylcholiny; 2-Naphthylamine; chemické modely; Phosphatidylcholines; Laurdan; TDDFT; Models, Chemical; DFT; Fluorescence; 2-naftylamin; kvantová teorie; classical molecular dynamics; 1,2-Dipalmitoylphosphatidylcholine